Transcriptional Profiles of Genes Related to Stress and Immune Response in Rainbow Trout (Oncorhynchus mykiss) Symptomatically or Asymptomatically Infected With Vibrio anguillarum - Hou, Zhi-Shuai; Xin, Yuan-Ru; Yang, Xiao-Dong; Zeng, Chu; Zhao, Hong-Kui; Liu, Meng-Qun; Zhang, Mei-Zhao; Daniel, Jeffrey G.; Li, Ji-Fang; Wen, Hai-Shen (Frontiers in Immunology, 2021)
Rainbow trout (Oncorhynchus mykiss) is one of the most common aquaculture fish species worldwide. Vibriosis disease outbreaks cause significant setbacks to aquaculture. The stress and immune responses are bidirectionally modulated in response to the health challenges. Therefore, an investigation into the regulatory mechanisms of the stress and immune responses in trout is invaluable for identifying potential vibriosis treatments. We investigated the transcriptional profiles of genes associated with stress and trout immune functions after Vibrio anguillarum infection. We compared the control trout (CT, 0.9% saline injection), asymptomatic trout (AT, surviving trout with minor or no symptoms after bacteria injection), and symptomatic trout (ST, moribund trout with severe symptoms after bacteria injection). Our results showed activated immunomodulatory genes in the cytokine network and downregulated glucocorticoid and mineralocorticoid receptors in both AT and ST, indicating activation of the proinflammatory cytokine cascade as a common response in AT and ST. Moreover, the AT specifically activated the complement- and TNF-associated immune defenses in response to V. anguillarum infection. However, the complement and coagulation cascades, as well as steroid hormone homeostasis in ST, were disturbed by V. anguillarum. Our studies provide new insights toward understanding regulatory mechanisms in stress and immune functions in response to diseases.